Co-production of MCR-1 and NDM-1 by Escherichia coli sequence type 31 isolated from a newborn in Moscow, Russia - Ofeliia Sulian; Vladimir Ageevets; Irina Lazareva; Vladimir Gostev; Dmitry Popov; Tatiana Vostrikova; Alexander Sukhinin; Yuri Lobzin; Sergey Sidorenko (International Journal of Infectious Diseases, 2020)
An Escherichia coli sequence type 31 isolate co-harbouring mcr-1 and blaNDM-1 genes on the plasmids of Incl2 and IncC groups, respectively, was recovered from a newborn with ventilator-associated pneumonia in Moscow, Russia. The convergence of polymyxin and carbapenem resistance and its expansion beyond Southeast Asia is a serious threat to human health.